Sleep habits and screen use in an adolescent population during the COVID-19 pandemic - Vieira, Paula Manuel; Cascais, Inês; Alba, Diana; Bernardo, Ana; Faria, João; Feio, Ana; Paiva Coelho, Margarida; Ribeiro, Maria do Céu; Gomes, Lúcia; Fonseca, Paula; et al. (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Introduction: Screen use among adolescents has increased, with excessive screen time associated with poor sleep. Isolation due to the COVID-19 pandemic may have exacerbated these problems. This study aimed to characterize adolescents’ sleep and screen use behaviors during the COVID-19 pandemic lockdown. Methods: This was a multicenter, cross-sectional, descriptive study of adolescents aged 10 to 18 years evaluated in an Adolescent Medicine outpatient visit of four hospitals in northern Portugal between January and March 2021. Adolescents completed a survey with questions about screen use and sleep and the Pediatric Daytime Sleepiness Scale (Portuguese version). Results: A total of 131 adolescents (66.4% female; median age 15 years) were enrolled during the study period. Participants reported a median sleep duration of nine hours on weekdays and 10 hours on weekends, with 25.9% sleeping less than eight hours on weekdays. Approximately 80% reported good or very good sleep quality. Onset insomnia was identified in 39.7% and excessive daytime sleepiness (EDS) in 13.7%. Most adolescents (74.0%) reported screen time of ≥6 hours/day. Screens were mainly used for attending classes and talking to friends. Smartphones were available in the bedroom at night for 83.2%, while 61.1% had televisions, 57.3% had computers, and 16.0% had gaming consoles in their bedrooms. Fifty-five percent used screens within an hour of bedtime every day. Screen time ≥6 hours/day and having a computer or smartphone in the bedroom at night were associated with shorter sleep duration on weekdays and EDS. Screen use within an hour of bedtime ≥4 times/week was associated with sleep-onset insomnia, shorter weekday sleep duration, and EDS. Discussion: Online classes during the COVID-19 lockdown may explain the use of devices ≥6 hours/day. Although most adolescents reported normal median sleep time and subjective good or very good sleep quality, screen use ≥6 hours/day and within one hour before bedtime was associated with sleep deprivation on weekdays and EDS. Conclusions: Excessive screen time during the pandemic appears to have had a negative impact on adolescents’ sleep. These findings underscore the importance of identifying and intervening in these issues when addressing adolescent global health.